Gen Z Perceptions And Expectations Of Culinary Quality And Service Transformation - Aan Nurhasanah; Rahmat Kusnedi; Kezia Elsty; Muhammad Irfan; Lilik Hariyanto; Dikki Z. Choesrani (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Gen Z's perceptions and expectations regarding the transformation of culinary quality and service are influenced by significant changes in food preferences influenced by social, cultural, and technological factors. Generation Z—born between 1997 and 2012—tends to try various types of food from different cultures and is very interested in innovation and sustainability in food. Generation Z prefers to try new foods and create unique flavor combinations. More than 70% of them admit to often trying foods they have never tried before, reflecting a desire to experience various flavors. Additionally, they are more likely to choose foods that align with personal values such as sustainability and health. Social media plays a significant role in shaping Generation Z's culinary preferences. They actively share their culinary experiences and often seek inspiration from food influencers on platforms like Instagram and TikTok. This shows that understanding food is very important in attracting the attention of this generation. The culinary industry faces the challenge of meeting the increasingly diverse demands of Generation Z. Companies must innovate in their products and services to attract the interest of Generation Z, including providing healthy and environmentally friendly food. Research results show that the main factor influencing consumer decisions to purchase products and services is their quality. About 60% of Gen Z customers feel dissatisfied with certain products and services. Generation Z hopes the culinary industry can respond to their demands, especially for new products and better services. Overall, Generation Z's perceptions and expectations regarding the transformation of culinary quality and service indicate that they are seeking satisfying dining experiences. They also want to contribute to the sustainability and ethics of the food industry, in line with the growing awareness of social and environmental issues. Keywords: Gen Z, Perception, Hope, Culinary Transformation, Food Quality, Service, Technology, Sustainability